2020
DOI: 10.5267/j.msl.2020.3.007
|View full text |Cite
|
Sign up to set email alerts
|

A study of factors influencing the price of apartments: Evidence from Vietnam

Abstract: The study investigates determinants important factors influencing apartment prices in Ho Chi Minh city, the biggest economic center of Vietnam. More especially, the study is conducted by collecting survey data of 124 apartments successfully traded during the first six months of 2019. Regression analysis results indicate that apartment prices were positively influenced by size of apartment, presence of balcony, presence of swimming pool, presence of shopping malls and periodic rental income or value. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This means that the estimation using the Ordinary Least Squares regression (OLS) does not provide a reliable result. Thus, robustness statistics is utilized for the estimation, following what have been suggested by White (1980) and recently performed by Bui (2020a). As can be seen from Table 4, the estimation results are significant at the 1% level (Prob>F = 0.000).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This means that the estimation using the Ordinary Least Squares regression (OLS) does not provide a reliable result. Thus, robustness statistics is utilized for the estimation, following what have been suggested by White (1980) and recently performed by Bui (2020a). As can be seen from Table 4, the estimation results are significant at the 1% level (Prob>F = 0.000).…”
Section: Resultsmentioning
confidence: 85%
“…In Vietnam, housing demand is highly increasing, especially in metropolitan areas Bui, 2020a;Nguyen and Do, 2020). This is because a great number of inter-provincial migrants tend to move to big cities (Bui, 2020b) while the availability of land is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the model that best satisfies the Pareto frontier is obtained, and the user can identify the most appropriate solution whose (i) CoD ensures a medium/high statistical robustness level, (ii) algebraic form is not too complicated to interpret, (iii) mathematical expression includes the largest number of variables considered capable to investigate the phenomenon addressed. This has often been used for analysis similar to that of the present research, regarding influencing factors in the market dynamics and the selling prices, or to identify the contribution of specific variables in the housing values formation processes [78][79][80][86][87][88], but never before to evaluate the effects of an extra-local exogenous event on the real estate market. In order to define a model (price function) that could efficiently describe the selling price formation mechanism for each study sample related to the six Italian cities considered for Phase I, the EPR-MOGA technique was implemented with no function f, through a static regression, a maximum number of equation terms equal to eight and a set of candidate exponents belonging to the range (0, 0.5, 1, 2).…”
Section: Econometric Techniquementioning
confidence: 99%
“…As far as the different dimensions and rooms of an apartment are concerned, Bui (2020) concluded that the prices of apartments are positively affected by the presence of a balcony, a pool, proximity to a shopping centre, and the possibility of renting. Bui (2020) states that these conclusions are valuable for apartment designers since they might offer better solutions to increase the value of the apartments and meet the customers' demands. In addition, Mohammadi (2010) states that the different rooms of the house impact its natural ventilation.…”
Section: Room Dimensions and Amenitiesmentioning
confidence: 99%